Development of nanodelivery systems for anti-tuberculosis drugs using metal hydroxides nanolayered hosts - Saifullah (2014)
Development of biocompatible and biodegradable nanodelivery systems with sustained release properties is the key research area of nanomedicine technology. Inorganic nanolayers are the promising material due to fascinating properties like ease of preparation, ability to intercalate different type of anions (inorganic, organic, biomolecules and even genes, etc.), high thermal stability, delivery of the intercalated anions in the sustained manner, high biocompatibility and easy biodegradation, etc. In this research, anti-tuberculosis (anti-TB) nanodelivery formulations were designed by intercalating anti-TB drugs into inorganic nanolayered hydroxide to be used as nanodelivery systems. Tuberculosis (TB) is an airborne infectious disease caused by Mycobacterium tuberculosis (MTB) and has been lethal to humans since centuries. Chemotherapy of TB involves multi-drug therapy, frequent dosing, and side effects of anti-TB drugs and long term treatment duration of 3-24 months. These complications are responsible for patients’ noncompliance to the treatment. Drug development is very lengthy, high budget consuming and multistage process and there has been no new anti- TB drug in the market since about the last 5 decades. Research on the development of drug delivery systems is of prime importance to overcome the above scenario. Drug delivery systems (DDS) offer many advantages over the conventional chemotherapy, such as targeted delivery and protection of drugs from physico-chemical degradation, which ultimately will reduce the side effects associated with drugs. The DDS releases the drugs in a sustained manner for a longer period of time that would result in the reduction in the dosing frequency. The nano-sized DDS have the tendency to easily penetrate the bacteria and cancer cells. All of these advantages would ultimately improve the patients’ compliance to the treatment. In this research, several anti-TB nanodelivery formulations were developed by intercalating anti-TB drugs namely para amino salicylic acid (PAS) and isoniazid (INH) into metal hydroxide nanolayers namely zinc layered (ZLH), zinc-aluminium layered double hydroxides (Zn/Al-LDHs) and magnesium-aluminium layered double hydroxides (Mg/Al-LDHs). A total of 8 nanocomposites based on the aforementioned anti-TB drugs and metal nanolayers hydroxides were prepared. The developed nanocomposites of anti-TB drugs with metal hydroxides nanolayers (inorganic nanolayers) showed higher biocompatibility with normal human lung cell lines (the most common residing place of mycobacterium tuberculosis) and with 3T3 mouse fibroblast cells (the most sensitive cells to toxicity). The release of the intercalated anti- TB drugs was sustained in human body simulated phosphate buffer (PBS) solutions of pH 7.4 and 4.8. Therapeutic efficacy of the anti-TB nanocomposites against mycobacteria tuberculosis was found to be much better compared to para amino salicylic acid and isoniazid in their free form. The in vitro study results are extremely encouraging to conduct the further study on animal models (in vivo study) and these biocompatible anti-TB nanocomposite formulations could be very useful in coping with tuberculosis effectively.